PENGARUH PROTEKSI CPO DENGAN FORMALDEHID TERHADAP KECERNAAN DAN PERFORMA DOMBA EKOR TIPIS - Nafly Comilo Tiven; Lies Mira Yusiati; Rusman (Rusman); Umar Santoso (Faculty of Animal Science, Universitas Gadjah Mada, 2015)
The experiment was conducted to determine the effect of CPO protected with formaldehyde on digestibility and performance of thin tail sheeps. Fifteen local male lambs aged 9-12 months, were divided into 3 groups of ration treatment. The first group received only the basal ration (R0), the second group received the basal ration and 3% CPO (R1), while the third group received the basal ration and 3% CPO protected with 2% formaldehyde (R2). The data were analyzed by Completely Randomized Design with oneway pattern. The different of treatments were tested by Duncan’s New Multiple Range Test. The results showed that addition CPO protected with formaldehid (R2) in the sheeps diet did not affect dry matter and organic matter intake, dry matter and organic matter digestibility, average daily gain (ADG), but significantly (P<0.01) increase feed conversion rate. It can be concluded that CPO protected with formaldehyde gives more advantage on feed conversion aspect.(Key words: Thin tail sheeps, Crude palm oil (CPO) protected with formaldehyde, Digestibility, Performance)